Discerning the Missio Dei in a Local Church’s Engagement with Its Community - Wieland, George M. (2020)
While theologies of missio Dei and their divergent missiological developments have been refined and contested in the academy over the past seven decades, the theoretical discussions and even the term itself are still far from commonplace in the life and discourse of many local congregations. Nonetheless, among such congregations there are examples of changing practice and new modes of local mission engagement that seem to be in alignment with aspects of a missio Dei orientation. In this article the experience of one congregation will be considered, asking whether a missio Dei perspective might be discerned in recent initiatives and developments in its engagement with its local community.
Keywords: Māngere; Māori and church; Local Church; Missio Dei; missional orientation; Postcolonial